Identifikasi Faktor Penyebab Kerusakan Sempadan Sungai (Studi Kasus: Sungai Pami, Distrik Manokwari Utara – Kabupaten Manokwari, Papua Barat) - Ceni Febi Kurnia Sari; Charly Bravo Wanggai (Fakultas Teknik, 2023)
Damage to the Pami Riverbank in the North Manokwari District, West Papua Province, is generally caused by the socio-economic and cultural activities of the community in the DAS (Daerah Aliran Sungai), which is a part of human intervention against natural systems in the DAS, such as development-cultivated land in the watershed. The increasing population growth and the demand for natural resources, including water, soil, land, and forests, can result in changes in watershed conditions. One of the buffer areas is the riverbank. The riverbank location functions as a buffer region at the proper and left components of the river. It provides ecological services for filtering runoff water and keeping nutrients and sediment that can be transported with floor runoff. The damage to the Pami River's borders becomes delivered about extra using natural elements, along with erosion, fallen bushes, landslides, and excessive river water discharges that motive cliff erosion in the middle and pinnacle reaches of the Pami River. Riverbank erosion occurs because of solid water runoff, in addition to the soil type factor in the Pami River, which is easily eroded due to the poor physical properties of the soil and is very sensitive to erosion and the soil slope factor.